First records of the rare eelpout Lycenchelys xanthoptera Anderson, 1991 (Teleostei, Zoarcidae) in the Ross Sea, Antarctica - Struthers, Carl D.; Møller, Peter R. (Zootaxa, 2009)
Six eelpout species (Zoarcidae) are currently known from the Ross Sea and adjacent areas: Dieidolycus leptodermatus Anderson, 1988; Lycodichthys dearborni (DeWitt, 1962); Ophthalmolycus bothriocephalus (Pappenheim, 1912); Pachycara brachycephalum (Pappenheim, 1912); Seleniolycus pectoralis Møller & Stewart, 2006 and Seleniolycus robertsi Møller & Stewart, 2006 (Anderson, 1990, 2006; Møller & Stewart, 2006). Zoarcidae is thereby one of the most diverse non-Notothenoid fish families in the Ross Sea.